Pilot Study of Quality of Diclofenac Generic Products Using Validated In-House Method: Indian Drug Regulatory Concern - Ahmed Nawaz Khan, Roop Krishen Khar, Malairaman Udayabanu (Journal of Applied Pharmaceutical Science, 2015)
Globally, the expanding issues over the extent of substandard or spurious medicines remain a challenge. It is operated largely by encompassing wrong therapeutic doses or adulterated formulations that necessitates routine monitoring to avoid any potential public health adversity. This study was aimed to determine the diclofenac sodium content in generic products available in northern Indian market. Therefore, 32 commercially available generic products of diclofenac sodium tablet were procured from the open market and subjected to assay evaluation using in-house developed and validated high performance liquid chromatography (HPLC) method. Product identification was confirmed by thin layer chromatography (TLC) method; and the quantitative results by validated in-house HPLC method showed 34.37% (11/32) products as out of Indian Pharmacopoeia specification including 15.62% (5/32) substandard products. This makes the health situation miserable for public and their trust. On comparing the assay with price of each tablet, it was noticed that quality of products was irrespective of price. People rely completely on manufacturer quality promises and on regulatory process. However, such substandard products which still exist in the market for use by the patient; unfortunately not identified yet, poses a serious issue and require some interventions to stop them in entering into market. So there is an urgent need to carry out the quality evaluation on regular and large scale by the state and national drug authorities to ensure better quality medicines.
Keywords: Diclofenac,Generic,Substandard,Drug Quality,Method Development,Regulatory Affairs.